2021
DOI: 10.24925/turjaf.v8i11.2388-2396.3680
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Commercial Insecticides against Tomato Leaf Miner Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) in Palpa, Nepal

Abstract: A survey and field experiment were conducted to evaluate the efficacy of commercial insecticides against tomato leaf miner [Tuta absoluta (Meyrick)(Lepidoptera: Gelechiidae)] under farmer’s field condition in Palpa, Nepal from February 2018 to April 2018. It consists of seven treatments replicated three times. The treatments included: Abamectin 0.15% EC (dose: 0.3ml/liter), Imidachloprid 17.8% SL (dose: 0.3ml/liter), Spinosad 45% SC (0.3ml/liter), Azadirachtin 300 ppm (5ml/liter), Chlorantraniliprole 18.5% SC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 7 publications
1
24
0
1
Order By: Relevance
“…While, biological insecticides kept also population of the pest in levels below ETL except the last week of the experiment. The similar results were obtained by (El-Sayed et al, 2015;Azzam et al, 2017;Taha et al, 2017;Bastola et al, 2020). Who found that voliam flexi caused the highest reduction rates, followed by chlorantraniliprole and Indoxacarb.…”
Section: The First Experimentsupporting
confidence: 85%
“…While, biological insecticides kept also population of the pest in levels below ETL except the last week of the experiment. The similar results were obtained by (El-Sayed et al, 2015;Azzam et al, 2017;Taha et al, 2017;Bastola et al, 2020). Who found that voliam flexi caused the highest reduction rates, followed by chlorantraniliprole and Indoxacarb.…”
Section: The First Experimentsupporting
confidence: 85%
“…As of late, T. absoluta has been formally announced in South Asian nations like India (in Maharashtra) during October 2014, and in Nepal and Bangladesh during May 2016, separately. Further, it was found in West Asian nations including Iran in 2010 (Bastola et al, 2020;Huda et al, 2020;Khani et al, 2020;Wakil et al, 2018). Subsequently, it then spread extremely quickly all through the Mediterranean shores, including regions for North Africa and the Middle East (Desneux et al, 2011;Hogea, 2020;Jac, 2017).…”
Section: Origin and Distributionmentioning
confidence: 98%
“…Tomato leaf miner, T. absoluta attacks the tomato plant in every possible stage and reduces the massive yields of the crops (Victor & Mwangi, 2019). Thus, it is perceived as a critical leaf mining, stalk borers, and fruit harming nuisance (Abdel-baky et al, 2021;Bastola et al, 2020;Jac, 2017). Throughout the country, it is a major factor behind the reduced production of tomatoes in both greenhouse and open field conditions (Gozel et al, 2020;Han et al, 2019;Munyua & Bream, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Tuta absoluta is a potentially very damaging pest and is difficult to control as it feeds inside the plant leaf and fruit and can develop resistance to several insecticides (Siqueira et al, 2000). Bastola et al (2021) during study reported Chlorantraniliprole to be the most effective insecticide against T.absoluta followed by spinosad and emamectin benzoate. Braham…”
Section: Chemical Managementmentioning
confidence: 99%
“…The major insect pests of tomato are tomato fruit borer (Helicoverpa armigera), leaf miner (Liriomyza trifolii), and whiteflies (Bemisia tabaci) which spreads tomato yellow leaf curl virus. Moreover, the tomato leaf miner (Tuta absoluta), has been recently introduced to Nepal in 2016 which can incur a huge loss in tomato production and has become an increasingly important pest with a huge loss in Nepal (Bastola et al, 2021, Joshi et al, 2017. This pest was recorded first time from Kathmandu valley in May 2016 and has been spread to the nearest districts to Kathmandu; Kavrepalanchowk, Dhading, and Nuwakot (Bajracharhya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%